Where are we in Consolidating the Administration of Shariah Criminal Justice? (Di Manakah Kita dalam Pemantapan Pentadbiran Keadilan Jenayah Syariah?) (Kanun: Jurnal Undang-undang Malaysia, 2015)
With the amendment of Article 121(1A) of the Federal Constitution, many considered the shariah courts to have been given more powers. Civil courts were also thought to no longer be able to intervene in matters decided by the shariah courts. However, with regard to criminal matters, the courts are still limited to the punishment of 5:3:6, namely, a fine of not more than RM5000 or imprisonment not more than 3 years, or 6 lashes. This article examines the power given to the shariah courts, and the effects on the development of the administration of shariah criminal justice and related agencies. Some suggestions are made to improve and to reinforce the Islamic administrative, judicial, prosecutory and enforcement institutions.Keywords: Federal Constitution, enforcement of shariah laws, shariah courts, civil courts